2014
DOI: 10.4238/2014.january.21.10
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity in the Dioscorea cayenensis/D. rotundata complex revealed by morphological and isozyme markers

Abstract: ABSTRACT.Of the 600 known yam species, only 10 are utilized as food, and the Dioscorea cayenensis/D. rotundata species complex is among the most cultivated. In Brazil, these species are commercially cultivated in the northeast region and are cultivated in the south and southeast regions as subsistence crops by traditional agriculturists. This study aimed to evaluate the genetic diversity of 21 local varieties of D. cayenensis and 2 D. rotundata accessions using 7 isozymic loci and 24 morphological markers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…rotundatacomplex ( Table 2). Bressan et al (2014) also evaluated 21 local varieties of D. cayenensis and two D. rotundata accessions using 7 isozyme loci and 24 morphological markers, and reported the existence of high genetic variability with 100% polymorphism using isozyme marker. Dansi et al (2000) and Mignougna et al (2002) also studied genetic diversity of D. cayenensis/D.…”
Section: Species Specific Issr Bands In D Cayenensis/d Rotundata Comentioning
confidence: 99%
“…rotundatacomplex ( Table 2). Bressan et al (2014) also evaluated 21 local varieties of D. cayenensis and two D. rotundata accessions using 7 isozyme loci and 24 morphological markers, and reported the existence of high genetic variability with 100% polymorphism using isozyme marker. Dansi et al (2000) and Mignougna et al (2002) also studied genetic diversity of D. cayenensis/D.…”
Section: Species Specific Issr Bands In D Cayenensis/d Rotundata Comentioning
confidence: 99%
“…However, AAT showed a higher level of genetic polymorphism than other markers in this study and previous studies. AAT is the most effective discriminant for some tuber crops with a higher level of polymorphisms than other isozymes markers (Efisue, 2013 andBressan et al, 2014). The isozyme marker analysis indicated that D. alata species were distantly related to D. rotundata and D. cayenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Isozymes, being biochemical expressions of the genetic make-up of the plant, can be used to greatly improve the accuracy of cultivar identification. Bressan et al (2014) used isozymes analysis in delineating yam cultivars into different species. The results revealed clear genetic diversity of the yam species between and within communities under study.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many available clustering methods, unweighted pair group method with arithmetic mean (UPGMA) has been the most used, due to the present higher values of cophenetic correlation coefficients, which measure the association between dissimilarty matrix and the cluster matrix (Mohammadi and Prasanna, 2003). For this reason, this method has been used in several studies that aim to characterize and assess the genetic variability of yams, such as those by Bressan et al (2014) and Efisue (2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, in other studies of genetic variability characterization of yams, UPGMA method has been used simultaneously with principal components and both are complemented by graphic dispersion analysis (Mwirigi et al, 2009;Norman et al, 2011;Michael, 2013;Mulualem and Michael, 2013;Siadjeu et al, 2015). These techniques are used in many studies of genetic variability characterization of yams (Mwirigi et al, 2009;Norman et al, 2011;Mulualem and Michael, 2013;Bressan et al, 2014;Efisue, 2015;Siadjeu et al, 2015). Thus, this study aimed to assess the genetic variability among genotypes of yam (D. rotundata), collected in four municipalities from the Recôncavo Baiano region, based on quantitative descriptors through multivariate methods.…”
Section: Introductionmentioning
confidence: 99%